The plight of Ukrainian refugees staying in Sweden under EU:s mass refugee directive: a brief trauma-focused, participatory, online intervention as a pilot feasibility study - Ekblad, Solvig; Gramatik, Oksana; Suprun, Yuliia (Frontiers in Digital Health, 2025)
BackgroundUkrainians staying in Sweden under the EU mass refugee directive may face challenges due to traumas caused by the invasion that started on February 24, 2022. Part of an European Social Fund (ESF) project, our study showed that a brief trauma-focused group intervention onsite helped to increase health and mental-health literacy. The intervention has not yet been adapted online.MethodsThis pilot study during six months aimed to investigate the feasibility, acceptability and outcome in perceived trust, anxiety/stress, and perceived health after this brief trauma-focused group intervention online. A second aim was to observe perceived acceptability of the group intervention with different ways of online intervention. Local coaches, interpreters, the authors, and local experts participated. A mixed-methods design with participatory methodology and evaluation were used. Data was collected with a short questionnaire in Ukrainian. Additionally, at the end of each set, we orally asked about perceived trust and integrity. There were six sets of five group sessions per set, a total of 30 sessions. Each group met online five times for 2 h, a total of 10 h excluding pre- and post-assessment. Breathing exercises sought to reduce stress among the participants.ResultsThe group intervention had both strengths and limitations. Baseline data were obtained from 136 participants, mostly females (75.7%). Answers to pre- and post-questionnaires showed that perceived anxiety/stress was significantly reduced (N = 91, chi-2 20.648, df = 6, p < .02). Perceived health significantly improved between pre- (mean 63.6) and post (77.2) (N = 77, t = −8.08, df = 66, p < .001). Older participants were vulnerable with higher stress and lower mean perceived health after the intervention. Four out of ten needed individual psychosocial support online.The participants' open questions were analyzed with qualitative content analysis, giving five general categories and 25 sub-categories and the theme “Strong efforts to cope with Swedish system”.ConclusionTrust and reduced anxiety level changed after the intervention and a combination online of small, closed group meetings with the possibility of personal acquaintance, trust and individual follow-up psychosocial support for those in need to be paid attention to for future refugee support services, particular an online format.